Aggregation and Evaluation of Vulnerabilities from CVE Databases for Effective Security Assessment - Tuček, Adam; Lazarov, Willi (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2025)
As digital technologies evolve, cyber threats continue to increase, often due to vulnerabilities in modern systems. This situation has led to the establishment of open databases and standardized methods for classifying, categorizing, and assessing software vulnerabilities. This paper addresses the domain of Common Vulnerabilities and Exposures (CVE) and introduces an innovative solution for aggregating CVE records to support security assessment and reporting.
Keywords: CVE; CWE; CVSS; CPE; vulnerabilities